Application of macro-heterogeneous composition materials for increase of endurance of tribological situations - A. S. Kalinichenko; V. Ja. Kezik; I. I. Krymchanskij; A. N. Savenok; N. L. Mandel (Литьë и металлургия)
The analysis of deferent types of composite materials has been performed. On this base the more suitable composite materials for conditions of BMZ have been chosen.